Antioxidant Activity- Synergistic Effects of Thymol and Carvacrol - Al-Mansori , Bubaker M.B Hamed; El-Ageeli, Wessal Hassan; Alsagheer, Seham Hamad Mohammed; Ben-Khayal , Faheem A. F (Al-Mukhtar Journal of Sciences, 2020)
This study was conducted to evaluate the antioxidant activity-synergistic effects of Thymol and Carvacrol using Three assays DPPH, FRAP, and TEAC. In the DPPH assay Carvacrol, Thymol and Carvacrol-Thymol mixture had scavenging activity and this activity increasing by increasing concertation from 50 to 1000ppm. Carvacrol showed a strong antioxidant activity than Thymol, and no synergistic effect in their mixture at tested concertation. In FRAP assay, Carvacrol had the highest antioxidant activity as in DPPH assay result. However, the mixture of Carvacrol and Thymol showed a higher reducing power than Thymol and no synergistic effect observed. In TEAC assay, Carvacrol showed a great quenching ability of ABTS radical cation than Thymol and the mixture both. The Carvacrol content in the mixture could be responsible for this higher antioxidant activity and there was no clear synergistic effect. These findings support that essential oils always contain a mixture of different chemical compounds. In addition to the major compounds, minor compounds may make a significant contribution to the total oil antioxidant activity.